2022
DOI: 10.1039/d1cp05490b
|View full text |Cite
|
Sign up to set email alerts
|

The binding mechanism of NHWD-870 to bromodomain-containing protein 4 based on molecular dynamics simulations and free energy calculation

Abstract: Bromodomain and extra-terminal (BET) proteins (BRD2, BRD3, BRD4, and BRDT) are epigenetic readers with tandem bromodomains. Small-molecule inhibitors of BET proteins are a promising treatment strategy against cancer. For example,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 97 publications
(105 reference statements)
0
6
0
Order By: Relevance
“…Hydrogen bonds formed between small chemical scaffolds of BET inhibitors and N140 (N433) of the acetylated lysine site of BRD4-BD1 (BRD4-BD2) are commonly required for binding of BET inhibitors. , Hydrogen bonding plays an important role in drug design. In particular, it plays a significant role in competitive inhibitor binding to the active site of the bromodomain of BET proteins, including BRD4-BD1 and BRD4-BD2 (Figure ). In this study, the hydrogen bond was confirmed when the distance between the acceptor and donor atoms was less than 3.5 Å, and the internal angle of the acceptor···H-donor was above 120°.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrogen bonds formed between small chemical scaffolds of BET inhibitors and N140 (N433) of the acetylated lysine site of BRD4-BD1 (BRD4-BD2) are commonly required for binding of BET inhibitors. , Hydrogen bonding plays an important role in drug design. In particular, it plays a significant role in competitive inhibitor binding to the active site of the bromodomain of BET proteins, including BRD4-BD1 and BRD4-BD2 (Figure ). In this study, the hydrogen bond was confirmed when the distance between the acceptor and donor atoms was less than 3.5 Å, and the internal angle of the acceptor···H-donor was above 120°.…”
Section: Resultsmentioning
confidence: 99%
“…A reliable inhibitor–protein complex structure plays a vital role in drug development. Computational methods, such as homology modeling, molecular docking, molecular dynamics (MD) simulation, binding free energy calculation, and others are widely employed. These methods were used to elucidate the binding models and mechanisms of inhibitor/BET systems. Thus, MD simulations and binding free energy calculations were employed in the present study to elucidate the selective-BD2 mechanism for the pyrrolopyridone core compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The calculated binding free energies presented in Table show that the nonpolar (i.e., hydrophobic) term plays the most important role in complex formation. Because the per-residue free energy decomposition strategy is known to enable analysis of the inhibitor–protein interactions, , the interaction energies between the various residues of FAK and VS-4718 were computed using the MM/GBSA decomposition protocol (Tables S5 and S6). As indicated by the obtained results, several hydrophobic residues possessed substantial subtotal binding free energies.…”
Section: Resultsmentioning
confidence: 99%
“…The MD simulations have become increasingly important in the context of understanding the interactions between receptors (e.g., proteins, enzymes, or cyclodextrins) and ligands (e.g., inhibitors, stabilizers, and supermolecules). ,, Therefore, MD simulations were carried out to explore the binding between VS-4718 and the FAK protein. The initial VS-4718/FAK complex structures obtained from the docking model were used as the initial complex conformations for subsequent simulations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation